Imagination et bande dessinée - María-Pílar Tresaco; Ana-Isabel Moniz (Carnets)
The front cover help developing our imagination to build the story we are going to discover. We analyze them to see if these covers "imagined" by the illustrators really have this function and if the reader's intuition, when looking at them, coincides with what the author, Jules Verne, and later the adapter wanted to transmit.